Fabrication of deep-sub-micrometer NbN/AlN/NbN epitaxial junctions on a Si-substrate. (5th November 2020) - Qiu, Wei; Terai, Hirotaka
Abstract: We have developed a novel fabrication process for ultra-small, full-epitaxial NbN Josephson junctions on a TiN buffered silicon (Si) substrate. We use an electron beam lithography for junction definition followed by a reactive-ion-etch (RIE). A chemical mechanical polishing process and an RIE by using CHF3 gas formed reliable electrical contacts for the junction electrodes. All junctions, with a junction size down to 0.27  μ m in diameter, showed excellent current–voltage characteristics with a clear gap and small sub-gap leakage current. We have confirmed that the quality of the junctions was maintained after the removal of the SiO2 dielectric interlayer.